Penerapan Perhitungan Pembiayaan Murabahah di Lembaga Keuangan Mikro Syariah BMT Sunan Drajat Pusat dengan Pendekatan Economic Value Of Time - Lidya Frasisca Ellyna; Abdullah Zawawi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Islam does not prohibit deferred financing, but it must be noted that in deferred financing one must be careful because Islam forbids the practice of usury and evil. The application of murobahah financing calculations is a calculation technique for calculating and determining the amount of customer installments to BMT Sunan Drajat. This study aims to answer, describe and analyze the formulation of the problem; 1) How is the application of murabahah financing calculations at BMT Sunan Drajat Pusat!. 2) How is the application of murabahah financing calculations with the economic value of time approach at BMT Sunan Drajat Pusat. This type of research uses qualitative research methods with a qualitative phenomenological approach. The data sources used are primary and secondary data. The research instruments used were observation, interviews and documentation. While the data analysis technique used is phenomenology including logical consistency, subjective interpretation and adequacy. The results of this study are 1) the application of murobahah financing calculations at BMT Sunan Drajat Pusat uses a flat system, this system is the same as a fixed margin system, meaning that the margin and principal installments are every month in the same amount from inception to maturity in accordance with the contract and mutual agreement of the BMT and the customer. 2) the application of the murobahah financing calculation using the economic value of time approach at BMT Sunan Drajat Pusat is in principle the same as the calculation of the flat system adopted by BMT Sunan Drajat Pusat because the total installments since the contract and agreement are the same as the due date, especially there are no additional customers who are late pay installments when they are due either margin or penalty.